Performance of Irradiated and Crosslinked Ethylene Vinyl Acetate-Waste Tire Dust Blend - Zainal Abidin, Anis Sakinah (2009)
The influences of electron beam irradiation, addition of crosslinking agents and the combination of irradiation and crosslinking agents on the properties of Ethylene Vinyl Acetate/Waste Tire Dust (EVA/WTD) blends were investigated. Trimethylolpropane triacrylate (TMPTA) and tripropyleneglycol diacrylate (TPGDA) were chosen as crosslinking agents. Blends were prepared by melt mixing in an internal mixer, Haake Rheomix Polydrive R600/610 at temperature and rotor speed of 140oC and 50 rpm, respectively. Studies in processing conditions were carried out in order to ensure the enhancement of EVA/WTD blend properties through irradiation. Results revealed that the optimum processing conditions were at 140oC mixing temperature, with 10 min of blending time and at 90/10 (EVA/WTD) blend ratio. The dynamic mechanical properties showed two glass transition temperatures that indicates incompatible blends. The introduction of electron beam irradiation on EVA/WTD at different doses, 50, 100, 150 and 200 kGy has enhanced the irradiation-induced crosslinking. Irradiation-induced crosslinking has increased with the increase in irradiation dose and lead to the improvement in tensile properties, compatibility, dynamic and thermal mechanical properties of the blends. The incorporation of TMPTA and TPGDA as crosslinking agents lead to the improvement of tensile strength, thermal and dynamic mechanical properties. A decline in tensile strength and dynamic properties of the EVA/WTD blend at above 50 kGy irradiation dose in the presence of TMPTA was observed. Such a decrease attributed to the embrittlement of the blend due to high extent of irradiation-induced crosslinking. TPGDA was found to serve the optimum tensile and dynamic mechanical properties upon EB irradiation of EVA/WTD blends.